Pengenalan E-Commerce Terhadap Umkm Desa - Laila Mucharomma; Labitha Intania Arifin; Enrico Julian Ekananda; Tri Yuli Ardiansyah (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Delik Sumber Village is a village located in Benjeng District, Gresik Regency, East Java Province. The socialization and implementation of e-commerce is carried out to help increase partner sales results. Based on the results of a field survey in the village of Delik Sumber, there are several types of MSMEs, namely food production, curtains, clothing, electronic services. Almost 80 percent of them experience problems in marketing their products and services, where sales results are not optimal because marketing methods are very limited. The method of activity used is by using direct observation and approaching business actors and implementing product marketing practices through e-commerce. This e-commerce activity has been carried out well, this is evidenced by the creation of various types of social media for MSMEs in the form of WhatsApp, Instagram, Facebook and others as a medium for promoting their business products. So that their business is widely known and certainly increases demand.Keywords: Delik Sumber Village, UMKM, E-Commerce.